Lack of interaction of the fluorosurfactant C6O4 with human renal transporters: In vitro/in silico analysis. (30th June 2022) - Bruno, Stefania; Bersani, Matteo; Astore, Serena; Chiabotto, Giulia; Barge, Alessandro; Binello, Arianna; Spyrakis, Francesca
Abstract: C6O4 is a water soluble perfluoroether carboxylic acid ammonium salt used as surfactant in the synthesis of fluoropolymers. Available experimental data in rats exposed by the oral route indicate it is eliminated in urine. Previous studies with various linear perfluorocarboxylic acids have suggested that these compounds are substrates of renal membrane transporters in rats and humans, and that the interaction with basal and apical membrane transporters can influence the elimination kinetic by these organisms and explain, in part, the observed differences in the respective half-lives. In particular, apical transporters may contribute to the reuptake of these exogenous compounds from the tubule lumen. The present study was designed to investigate the uptake of C6O4 in two renal cell lines transiently transfected with the human apical membrane transporters, organic anion transporter 4 (OAT4), and urate transporter 1 (URAT1). The uptake of the linear perfluorohexanoic acid (PFC6) was evaluated in parallel. While the uptake of the conjugated steroid estrone-3-sulfate (E3S), a known substrate for renal transporters, and of PFC6 was clearly observed in both cell types transfected with either OAT4 or URAT1, no significant uptake of C6O4 was measured under the same test conditions. The results of the transporter's functionality measured in vitro were consistent with molecular docking simulations. Both outward and inward models of the transporters showed a reduced interaction between C6O4 and URAT1 or OAT4. In contrast, more stable interactions were predicted for PFC6 and PFOA, as well as for the E3S substrate, as shown by the respective docking scores reflecting the binding strength and by the poses assumed in the transporter channels. Altogether, the in vitro and in silico modeling results showed a low reuptake potential and limited interactions of C6O4 molecule with two human apical membrane transporters, contrasting with the more efficient reuptake of PFC6 from the tubule lumen. These results suggest reabsorption from the proximal tubule by apical renal transporters is not likely to interfere with the elimination pathway of C6O4 in humans. Graphical Abstract: ga1 Highlights: C6O4 treatment does not affect the proliferation of human tubular cells. C6O4 is not absorbed into the renal cells expressing URAT1 and OAT4. C6O4 has a limited interaction with URAT1 and OAT4 transporters. URAT1 and OAT4 do not mediate reuptake of C6O4. Renal reabsorption does not play a significant role in renal elimination of C6O4.